The Use of Youjigo Vocabulary on Instagram: A Sociolinguistic Analysis of the Account @uuui_ycoo - Kurniawati, Heny (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2024)
This study aims to analyze the use of